Knowledge and practices of Village Health Team members in early detection and care for children with severe acute malnutrition at the community level: A case study in rural Uganda - Kemigisha, Elizabeth; Atwine, Daniel; Orikiriza, Patrick; Natukunda, Naome; MacDonald, Noni E. (Canadian Public Health Association, 2016)
Malnutrition remains a serious problem for young children in many developing countries. In Uganda, high malnutrition rates have been reported in the southwest region where 40% of children have chronic malnutrition, 5% with acute malnutrition. Community-based Village Health Teams (VHTs) with very basic health knowledge provide the first level of government-supported health care. WHO (World Health Organization) recommends community management of malnutrition, but little has been documented on the role of VHTs in this regard. We carried out a survey to compare VHTs in two rural communities in terms of: knowledge in food classification, malnutrition detection using MUAC (mid upper arm circumference) tape, and VHT advice on breastfeeding options for those with HIV. We also documented the challenges faced in community management of malnutrition
Keywords: Village Health Team members; Early detection and care for children; Severe acute malnutrition; Uganda